A large hadrosaur from Presa San Antonio, Cerro del Pueblo Formation, Coahuila, Mexico - Rivera Sylva, Hector; Reyna Hernández, Rogelio Antonio; Silva Martínez, Luis Encarnación; Guzmán Gutiérrez, Rubén (2021)
New hadrosaurid postcranial material is reported, collected near Presa San Antonio, Parras de la Fuente municipality, Coahuila, Mexico, in a sedimentary sequence belonging to the upper Campanian of the Cerro del Pueblo Formation, in the Parras Basin. The skeletal remains include partial elements from the pelvic girdle (left ilium, right pubis, ischium, and incomplete sacrum), a distal end of a left femur, almost complete right and left tibiae, right metatarsals II and IV, cervical and caudal vertebrae. Also, partially complete forelimb elements are present, which are still under preparation. The pubis shows characters of the Lambeosaurinae morphotypes, but the lack of cranial elements does not allow us to directly differentiate this specimen from the already described hadrosaurid taxa from the studied area, such as Velafrons coahuilensis, Latirhinus uitstlani, and Kritosaurus navajovius. This specimen, referred as Lambeosaurinae indet., adds to the fossil record of the hadrosaurids in southern Laramidia during the Campanian.